Fluorescence ureteral navigation during laparoscopic surgery for clinically suspected stage T4 colorectal cancer: A cohort study. (March 2022) - Ryu, Shunjin; Hara, Keigo; Okamoto, Atsuko; Kitagawa, Takahiro; Marukuchi, Rui; Ito, Ryusuke; Nakabayashi, Yukio
Abstract: Background: Approximately 15% of patients with colorectal cancer present with locally advanced tumors (T4 stage). Laparoscopic surgery for stage T4 disease has not yet been established. The near-infrared ray catheter fluorescent ureteral catheter (NIRFUC) is a new device that uses near-infrared fluorescence resin. We examined the utility of fluorescence ureteral navigation (FUN) with the NIRFUC during laparoscopic surgery for stage T4 colorectal cancer. Materials and methods: Patients with stage T4 colorectal cancer (n = 143, from January 2017 to March 2021) were divided into a T4FUN + group, in which the NIRFUC was used (n = 21), and a T4FUN- group, in which the NIRFUC was not used (n = 122). Short-term outcomes were compared between the groups. Next, the laparoscopic surgery rate and incidence of ureteral injury from January 2017 to March 2021 were compared between the T4FUN- group and the non-stage T4FUN- group (n = 434, from January 2017 to March 2021), in which fluorescence ureter navigation was not used. Results: Rectal cancer, stage T4b disease, and invasion into the urinary tract were observed more often in the T4FUN + group than in the T4FUN- group. In the comparisons of the T4FUN + versus T4FUN- groups, the operative time was 398 (161–1090) vs. 256 (93–839) minutes, the blood loss was 10 (1–710) vs. 25 (0–1360) ml, and the ratio of laparoscopic surgery to open surgery was 21:0 vs. 79:43. Postoperative complications (Clavien-Dindo grade ≥ III) were present in 2 (10%; 0 ureteral injury) patients in the T4FUN + group and 13 (11%; 2 ureteral injury) patients in the T4FUN- group. In the T4FUN + group, the operative time was longer (p < 0.0001), but the laparoscopic ratio was higher (p = 0.0002), and the blood loss volume and incidence of ureteral injury tended to be lower. In the comparisons of the T4FUN- versus non-stage T4FUN- groups, the ratio of laparoscopic surgery to open surgery was 79:43 vs. 384:50, the incidence of open conversion was 8 (6.6%) vs. 15 (3.5%), and the incidence of ureteral injury was 2 (1.6%) vs. 0 (0%). In the T4FUN- group, the open surgery rate (<0.0001), open conversion rate (p = 0.0205) and incidence of ureteral injury (p = 0.0478) were high, with a significant difference observed between the groups. Conclusion: Patients with stage T4 disease have an increased risk of ureteral injury and are more likely to be converted to open surgery. FUN can help to safely increase the laparoscopic surgery rate while safely visualizing the ureter. FUN is recommended for laparoscopic surgery in patients with stage T4 colorectal cancer. Clinical trial registration: Examination of fluorescence navigation for laparoscopic colorectal cancer surgery; Research Ethics Committee of the Kawaguchi Municipal Medical Center (Saitama, Japan) approval number: 2020-3. https://kawaguchi-mmc.org/wp-content/uploads/clinical research-r02.pdf ; Highlights: Fluorescence ureteral navigation with the NIRFUC improves the visibility of the ureter. Selection of patients for which to use the NIRFUC is important. Laparoscopic colorectal surgery for stage T4 cancer has a risk of ureteral injury. Fluorescence ureteral navigation is recommended for laparoscopic T4 colorectal cancer surgery. The NIRFUC may contribute to a reduction in ureteral injury and increase laparoscopic surgery.